CREACIÓN DE LA RUTA TURÍSTICA EN EL CANTÓN TENA, PROVINCIA DE NAPO - Dahua Shiguango, Bladimir Jairo (2018)
Ecuador is a country that has great cultural and natural diversity in its four regions. It is considered one of the twelve most biodiverse countries on the planet and the number one if one considers the density of biodiversity per square meter. From its mountain ranges born the main watersheds of the country, which become tourist attractions that generate interest of people at national and international level. Tena is one of the five cantons that make up the Province of Napo and the provincial capital. It has a diversity of natural sites and cultural manifestations that are located in each of the parishes. Due to the cultural and natural tourist attractions of Tena Canton, which are not being properly valued and exploited, it was important to develop this research work that aims to promote and promote greater attention and importance to the tourism sector, which in the future it will be reflected in the increase in tourists, which will boost the economy of the canton, which is why it allowed to carry out the present research work, for which the general objective was stated: "Creation of the tourist route in Canton Tena, Province of Napo "; In order to develop the general objective, three specific objectives were set: the first one was to "Establish the tourist diagnosis for the tourist route of the Tena Canton, Napo Province", for which the analytical method was used that allowed an analysis of the reality of each one of the tourist attractions of the canton; In the same way, the synthetic method was used to synthesize the information from the previous method and verify the facilities and difficulties with which the canton has, the inductive method allowed to determine the economic and social impact on the sector involved in the development of the project ; and, the deductive method allowed to elaborate the respective conclusions of the problem, needs and proposals. In addition, the Tourist Diagnostic Matrix of Carla Ricaurte Quijano, interview techniques, direct observation, tourist inventory files of the Ministry of Health were used in the process. Tourism (MINTUR), files of hierarchy of attractions of the Ministry of Tourism, and support material obtained from the Plan of Development and Territorial Ordering of Tena Canton and its parishes; the document facilitated the collection of political, social, economic, geographic and tourist information, to conclude the SWOT matrix was used, allowing to identify factors such as the strengths, weaknesses, opportunities and threats of the canton. The second objective: "Design the tourist route for the Tena Canton, Napo Province" for this purpose, the GPS device was used to take georeferencing points that determine the latitude, longitude and altitude as well as the distances and times between attractions and tourist services that will be included in the route; camera for digital support and the Matrix of the Ministry of Tourism to validate tourist routes; In addition, pictograms of natural, cultural attractions, tourist activities and support service for the design of the map were used. To conclude, an identifying mark was designed for the route called "Tena Capital Tourist Route of the Guayusa y Canela", for which the itinerary with its respective tourist script was established. 5 The third objective: "Propose strategies for the tourist route of the Tena Canton, Napo Province". For this purpose, strategies were considered in two phases; The first strategy was to design promotion and dissemination materials; within which was included the design of a totem, triptych, t-shirts and souvenirs; The second strategy was the design of a tourist package to propose the commercialization to the retail travel agencies of the country. Finally, the conclusions and recommendations of the thesis project were established in which it is determined that the success of the project will depend on the distribution channel that is obtained.